Teaching Method Used by English Teachers during Covid-19 Pandemic and New Normal Era - Marni Bawawa; Seli Marlina Radja Leba; Rezky Uspayanti (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
Teaching method selection is one of the factors in achieving learning objectives. This study aims to find out and analyze the use of teaching methods used by English teachers of Senior High School District Merauke. Some English teachers were the subject of this research that was taken from 4 Senior High School District Merauke. Selecting the sample used purposive sampling. This study used qualitative descriptive analysis. In collecting the data, researchers used interviews. Based on the result of the interview, the English teachers used a variety-teaching method in the teaching and learning process both online and offline learning. The teaching method was used by the teachers namely blended learning method, project-based learning, learning and playing, Audio Lingual Method, Total Physical Respond, Grammar-Translation Method. Furthermore, the English teacher also used applications from google such as GC (Google classroom), GM (Google meet), and GD (Google Docs). In teaching during a pandemic covid-19 and new normal, English teachers also used picture media as a tool in the teaching and learning process.